49 Endogenous Effects of Leptin on Leydig Stem Cell Differentiation through Desert Hedgehog Signaling Pathway. Issue 1 (1st April 2022) - Seetharam, D; Qureshi, R; Khodamoradi, K; Parmar, M; Van Booven, D; Vedenko, A; Farber, N; Arora, H; Ramasamy, R
ABSTRACT: Introduction: Although testosterone deficiency (TD) may be present in 1 out of 5 men 40 years or older, the factors responsible for TD remain largely unknown. Leydig stem cells (LSCs) differentiate into adult Leydig cells (ALC) and produce testosterone in the testes under the pulsatile control of luteinizing hormone (LH) from the pituitary gland. However, our recent studies have suggested that the testicular microenvironment (TME), which is comprised of Sertoli and peritubular myoid cells (PMC), plays an instrumental role in LSC differentiation and testosterone production under the regulation of the desert hedgehog signaling pathway (DHH). In the present study, we hypothesized that testicular TME releases paracrine factors that modulate LSC differentiation. Objective: To further examine the TME its see if its release of paracrine factors modulates LSC differentiation. Methods: A total of 13 men with testicular failure underwent testis biopsies for sperm retrieval. Using an IRB approved protocol, about 10mg of testicular tissue from each of these men were processed for Leydig stem cell isolation, culture and characterized. Cytokine antibody array was performed to identify the paracrine factors released by TME. The cells were treated with hedgehog signaling agonist and antagonist in the presence or absence of identified paracrine factors from the conditioned media. Two independent biopsies were treated with siRNA against LEPR (25pmol) for 48hrs. This was followed by evaluating the extent of knockdown on LEPR and B3HSD. Further, to evaluate the functional aspects (cell proliferation) modulated by Leptin-DHH signalling by first sorting the Sertoli cells, Peritubular myoid cells, Leydig stem cells and Adult Leydig cells using surface markers. These cells were then treated with Hedgehog agonist (SAG) and antagonist (Vismodigib), in the presence or absence of increasing doses of Leptin (0, 1, 10 ng/ml respectively) 48 hours post treatment, these cells were used for checking the impacts of Leptin-DHH treatments on cell proliferation by MTT assay. GraphPad Prism (GraphPad Software) was used for statistical analysis. All data were presented as the means ± SEM. The statistical significance between two groups was estimated by unpaired two-tailed t-test. Results: We successfully isolated and cultured up to 5 × 106million LSC's / biopsy from all 13 human testis biopsies. These cells were characterized for the presence or absence of different cell types in testis such as adult Leydig cells, Leydig stem cells, Sertoli cells, peritublar myoid cells and germ cells. Results showed that, of the cells cultured, up to 70% of the cells were Leydig stem cells and 10% of them were Sertoli-cell in origin on day 14. IF and qPCR data showed as the majority of cell population was undifferentiated (PDGFR-α). Upon stimulation by LH, the expression of 3βHSD (mature Leydig cells) was increased and that of PDGFR-α was decreased. Results from siRNA against LEPR has shown the down-regulated LEPR and B3HSD expression levels. The results from cell proliferation showed that there is minimal to no impact of leptin treatment on upon DHH agonist (SAG) or antagonist (Vismodigib) treatment in either cell types therefore suggesting that Leptin is not involving in the proliferation mechanism. Furthermore, the results demonstrated that TME secretes leptin which induces LSC differentiation and increases T production. Leptin's effects on LSC differentiation and T production, however, are inversely concentration-dependent: positive at low doses and negative at higher doses. Mechanistically, leptin acts on LSCs upstream of DHH; leptin-DHH regulation functions unidirectionally insofar as DHH gain or loss of function has no effects on leptin levels. Conclusions: Taken together, results from this study demonstrate the instrumental role of leptin as a paracrine factor secreted by TME on human LSC function and differentiation. Moreover, this study established the molecular events (DHH signaling) that underlie the leptin-modulated effects on LSCs. Further studies are ongoing to validate the implications of these Leptin in terms of its role in LSCs function, differentiation and survival Disclosure: No